Customers' choice towards aftersales serviceability of counterfeit spare parts: a case study / Syahrul Nizam Samsudin, Bulan Abdullah and Noriah Yusoff - Samsudin, Syahrul Nizam; Abdullah, Bulan; Yusoff, Noriah (Universiti Teknologi MARA Press (Penerbit UiTM), 2024)
A case study was conducted to examine Malaysian perceptions of product origin in connection to counterfeit components of Perusahaan Otomobil Nasional Sdn Bhd (PROTON). Some consumers regard the price of spare parts at service centres as costly, while others find it affordable. This view is formed based on individuals' prior experience with original equipment manufacturer (OEM) components and the imitation parts found at non-certified service centres. The study evaluates the customers’ perception levels and the correlations of customer choice characteristics (CCC) with country of origin (COO) image towards countries that produce counterfeit spare parts, such as China, Taiwan, and Thailand. This paper adopts a phenomenological perspective and measures how customers perceive the value of their choice towards the selected country of origin. We conducted a survey among 201 PROTON customers. The findings of the study revealed that PROTON customers are more favourable towards accepting counterfeit automotive spare parts from Taiwan compared to China and Thailand in both categories, CCC and COO. The correlation evaluation was done according to Pearson’s Coefficient, which affirmed that Taiwan earns a moderate positive correlation coefficient between +0.5 and +0.7 of all 6 variable components of both CCC and COO, namely willingness to buy, attitude towards products, product evaluation, country belief, people's affect, and desired interaction. While correlation for both China and Thailand indicated a weak relationship between CCC and COO of coefficient less than 0.5 for similar variable components, all components of the CCC have a positive relationship with the COO, with all variables moving in the same direction for all three countries. Also, Taiwan’s counterfeit spare parts scored high positive perceptions among the respondents on the level of agreement and satisfaction attributes. On the contrary, this customer acceptance grants Taiwan’s spare parts manufacturers the opportunity to consider investing in the Malaysian market.